Sugar, Taxes, & Choice - Véliz, Carissa (The Hastings Center report, 2019)
Population obesity and associated morbidities pose significant public health and economic burdens in the United Kingdom, United States, and globally. As a response, public health initiatives often seek to change individuals’ unhealthy behavior, with the dual aims of improving their health and conserving health care resources. One such initiative—taxes on sugar-sweetened beverages—has sparked considerable ethical debate. Prominent in the debate are arguments seeking to demonstrate the supposed impermissibility of SSB taxes and similar policies on the grounds that they interfere with individuals’ freedom and autonomy. Commentators have often assumed that a policy intended to restrict or change private individuals’ consumption behavior will necessarily curtail freedom and, as a corollary, will undermine individuals’ autonomy with respect to their consumption choices. Yet this assumption involves a conceptual mistake. To address the misunderstanding, it’s necessary to attend to the differences between negative liberty, freedom of options, and autonomy. Ultimately, concerns about negative liberty, freedom, and autonomy do not provide strong grounds for opposing SSB taxes.